A Comparison Between "Fan Fiction" and "Professional Fan Fiction" - Clerc, Sue (2006)
Keywords: dept.lib; faculty_collection; sabbatical_report

Saints, Clergy, and Other Religious Figures on Film and Television, 1895-2003 - Paietta, Ann Catherine (McFarland & Co., McFarland & Company, 2005)
"This work details over 900 films and TV series made from the 1890s through 2003 in which a religious figure plays a prominent or recurring role, or in which a character poses as a religious figure"–Provided by publisher.
Keywords: Catalogs; Catalogs; Television programs; Saints in motion pictures; Clergy in motion pictures; Saints on television; Clergy on television; Religion in motion pictures; Religion on television; Motion pictures; dept.lib; faculty_collection

American Indian and African American People, Communities, and Interactions an Annotated Bibliography - Bier, Lisa (Praeger, 2004)
Interest in this topic is growing rapidly, both as a field of academic research and as people with African American and American Indian backgrounds voice interest in their heritage. Materials on this topic are often difficult to locate because of the ways that libraries and research databases organize information. This bibliography is the first of its kind and strives to make researching this understudied topic easier. This volume will serve as an important research tool in this area. This bibliography features books, articles, Web sites, and videos containing information on interactions betwe
Keywords: Bibliography; Bibliography; African Americans; Bibliography; Indians of North America; History; Mixed descent; Relations with Indians; United States. Army. Cavalry; 10th; dept.lib; faculty_collection

Social bookmarking for organization, discovery, and publication - Hedreen, R.C. (Journal of Library and Information Services in Distance Learning, 2006)
Keywords: dept.lib; ⛔ No DOI found

Exploring virtual librarianship: second life library 2.0 - Hedreen, Rebecca; Johnson, Jennifer L; Lundy, Mack A; Burnette, Peg; Perryman, Carol; van den Brekel, Guus; Jacobson, Jj; Gullett, Matt; Czarnecki, Kelly (Internet Reference Services Quarterly, 2008)
In April 2006, Alliance Library System and Online Programming for All Libraries partnered to start the Second Life Library 2.0 in the online world Second Life and in August 2006 purchased an island on the Teen grid of Teen Second Life. Second Life is a virtual world, a descendant of multiplayer online games. Educational institutions have recently been drawn into Second Life's robust economy and vibrant cultural life. The Second Life Library 2.0 works with librarians from around the world and with other educational partners such as TechSoup, WorldBridges, and the New Media Consortium. Second Life Library 2.0 provides traditional library services such as ready reference, book discussions, and search assistance, but, at heart, it explores what it means to be a virtual library in a virtual world.
11 citations (Crossref) [2023-10-31] Citation Key Alias: pop00099 tex.type: [object Object]
Keywords: Library 2.0; Online Collaboration; Online Education; Second Life; Virtual Librarians; Virtual Libraries; Virtual Worlds; dept.lib